Discriminant validity of spatial and temporal postural index in children with neurodevelopmental disorders. Issue 1 (3rd July 2017) - Bucci, Maria Pia; Goulème, Nathalie; Stordeur, Coline; Acquaviva, Eric; Scheid, Isabelle; Lefebvre, Aline; Gerard, Christophe‐Loïc; Peyre, Hugo; Delorme, Richard
Abstract: Autism, learning disabilities and attention deficit/hyperactive disorder are often comorbid disorders. In order to try and find some markers that might be transnosographic, we hypothesized that abnormal postural sway profiles may discriminate children with neurodevelopmental disorders (NDDs) from typically developing children. The aim of our study was thus to compare spatial and temporal measures of the Center of Pressure in three distinct groups of children with NDDs (high functioning autism spectrum disorders, learning disabilities (dyslexia) and attention deficit/hyperactive disorders) and in typically developing children. Postural performances were thus evaluated in 92 children (23 per group, sex‐, age‐ and IQ‐matched groups) by using the Multitest Equilibre platform (Framiral ® ). Two viewing conditions (eyes open and eyes closed) were tested on a stable and unstable platform. Results reported similar poor postural instability for the three groups of children with NDDs with respect to the typically developing children, and this was observed for both spatial as well as temporal analysis of displacement of the center of pressure. Such postural instability observed in children with NDDs could be due to impairment in using sensorial inputs to eliminate body sway, probably due to poor cerebellar integration.